1960
DOI: 10.1161/01.cir.21.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium and the Electrocardiogram in Hypokalemia

Abstract: A definite correlation can be established between the electrocardiogram and the serum potassium level at hypokalemic levels. A study was made at the Mayo Clinic of 130 hypokalemic patients with relatively stable clinical states. Variations in Q-T intervals, P-R intervals, atrial rhythm, P waves, T/R values, and T-wave and U-wave contour in hypokalemia were noted as were the relationships between the T-U complex, electrical repolarization phenomena and potassium metabolism. Since modifying factors such as drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1
1

Year Published

1963
1963
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 63 publications
2
35
1
1
Order By: Relevance
“…We found that doses lower than those used for 1-: F'T-l .1 I I., V nebuliser therapy (2.5-5.0 mg) produced marked hypokalaemic and ECG effects in normal subjects. The ECG effects of salbutamol were consistent with changes due to either hypokalaemia or hypomagnesaemia (Weaver & Burchel, 1960;Eisenberg, 1986). High dose inhaled salbutamol may produce small falls in plasma magnesium (Lipworth et al, 1988a) although levels were not measured here.…”
Section: Discussionmentioning
confidence: 76%
“…We found that doses lower than those used for 1-: F'T-l .1 I I., V nebuliser therapy (2.5-5.0 mg) produced marked hypokalaemic and ECG effects in normal subjects. The ECG effects of salbutamol were consistent with changes due to either hypokalaemia or hypomagnesaemia (Weaver & Burchel, 1960;Eisenberg, 1986). High dose inhaled salbutamol may produce small falls in plasma magnesium (Lipworth et al, 1988a) although levels were not measured here.…”
Section: Discussionmentioning
confidence: 76%
“…The T wave, representing final repolarization, has been linked to dispersion of repolarization across the ventricular wall (40). However, the preferential appearance of bifurcated T waves in leads II and V 3 during hypokalemia (39) suggests that the predominant heterogeneity during hypokalemia may be regional rather than transmural.…”
mentioning
confidence: 99%
“…Arrhythmias, including ventricular extrasystoles and ventricular bigeminy, have been consistently observed by Surawicz and Lepeschkin [16] when the potassium values are below 2.6 meq./l, and disappear after administration of potassium. Weaver and liurcheU found extrasystoles with a potassium below 3.6 meq./l in 24% of normotensive and in 30% of hypertensive pa tients [18]. Ventricular tachycardias have been encountered in pa tients with potassium depletion following infusion of glucose with a relatively small amount of potassium [4,12].…”
Section: Discussionmentioning
confidence: 99%